CRITICISM CITY SPACE ARCHITECTURE: A CASE STUDY FISH LANDING STATION OF PAOTERE, MAKASSAR CITY - Sriany Ersina (Teknosains, 2021)
Makassar City as the capital city of South Sulawesi province has the potential and opportunity to develop its fishery industry to become the center of the largest fishery industry in Eastern Indonesia. One of the fishing ports in Makassar City is a Paotere fish landing station. The Paotere fish landing station is in the northern part of Makassar City and is located on Jl. Sabutung I No.3, Kelurahan Gusung, Ujung Tanah District, Makassar City and is the center of a fishing port that has many activities and is related to fish auction needs, such as auction, fish unloading, and ship supplies. This study aims to identify fish landing base areas in the city of Makassar, and in general, can be a reference for the Makassar City Government in determining development strategies in planning and designing fish landing bases in Makassar and Sulawesi cities. This study is based on a rationalistic descriptive paradigm with a normative architectural criticism approach which refers to the urban design elements of Hamid Shirvani's theory (grand concept / grand theory). The results of this study indicate the need for planning and redesigning the Paotere fish landing station area in Makassar city.